A Study of the Separation of Fibrinogen and Antihemophilic Factor (AHF) in Canine, Porcine, and Human Plasmas - Wagner, Robert H.; Richardson, Bobby A.; Brinkhous, K. M (Thrombosis and Haemostasis, 1957)
1. Studies are reported on attempts to separate antihemophilic factor (AHF) from fibrinogen in plasma by selective adsorption with fuller’s earth, aluminum hydroxide gel, and Seitz filtration.2. Fuller’s earth adsorption of canine plasma resulted in almost complete removal of fibrinogen without loss of AHF. By the use of this procedure as part of the fractionation procedure, potent AHF fractions free of fibrinogen have been obtained.3. Al(OH)3 adsorption of fibrinogen from bovine, canine, and human plasmas is greater than the adsorption of AHF. Al(OH)3 adsorption offers promise for the preparation of fibrinogen-poor AHF fractions of human or bovine plasma.4. Seitz filtration of plasma causes loss of AHF with little or no loss of fibrinogen.